1992
DOI: 10.1002/pola.1992.080300817
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated imidization reactions using microwave radiation

Abstract: SYNOPSISMicrowave radiation has been clearly shown to result in enhancement of the rate of reaction for an imidization reaction. Analysis of the kinetic parameters showed that the apparent activation energy for the reaction was reduced from 105 to 55 kJ/mol, under the conditions of this experiment. The mechanism which has been proposed to explain this enhancement is based on the concept of a nonuniform temperature on a molecular scale, rather than a true reduction in the activation energy. 0 1992 John Wiley & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(101 citation statements)
references
References 4 publications
3
97
0
1
Order By: Relevance
“…To our knowledge, only few papers on organic syntheses under MI at low temperature have been reported. Bose et al (1991), Sun et al (1988) and Lewis et al (1992) reported the athermal action of MI on organic synthesis at low temperature. Huang et al (1996a b) studied the kinetics theory of MI on chemistry synthesis at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only few papers on organic syntheses under MI at low temperature have been reported. Bose et al (1991), Sun et al (1988) and Lewis et al (1992) reported the athermal action of MI on organic synthesis at low temperature. Huang et al (1996a b) studied the kinetics theory of MI on chemistry synthesis at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…entropic effects) are related to the orientation of the reacting molecules to the electric field and consequently facilitate the reaction pathway. These latter "microwave effects" have been a topic of debate where many authors in the mid-90s argued that the presence of an electric field leads to orientation effects of dipolar molecules to influence the pre-exponential factor [69] or activation energy [70] in the rate coefficient. However, we believe that these "special effects"…”
Section: Batch Experiments Using Conventional and Microwave Heatingmentioning
confidence: 99%
“…Consequently, a faster nucleation rate is expected in this case, reducing the probability of heterogeneous nucleation. In addition, it must be noticed that in the WW assisted heating mode, a dielectric heating of the positive and negative ions and polar molecules of solvent (Lewis et al 1992) takes place, which is originated from the dissipation of energy into heat as an outcome of agitation and intermolecular friction of molecules when dipoles change their mutual orientation at each alternation of the electric field at a very high frequency (Nyutu et al 2008). It has been argued (Zhu et al 2010) that as a consequence of such dielectric heating, after the nucleation stage, most of the precipitating ions are distributed around nuclei well-proportioned, which facilitate the growth of each orientation yielding well crystallized particles.…”
Section: Synthesis and Characterization Of Nanophosphorsmentioning
confidence: 99%